Перекись водорода — эндотелиальный фактор расслабления в каротидных артериях гуся - Яковенко, И.Н.; Жирнов, В.В. (Доповіді НАН України, 2010)
Показано, що iнгiбiтори гемвмiсних бiлкiв (NaCN i Na2S) блокували NO-залежне розслаблення, але не впливали на EDHF-компонент ацетилхолiнової вазорелаксацiї, що виключає участь гемвмiсних ферментiв як EDHF-синтаз. Каталаза i 2-меркаптоетанол пригнiчували EDHF-опосередковане розслаблення. Екзогенна H2O2 у дiапазонi концентрацiй вiд 10 до 100 мкмоль/л викликала ендотелiй-незалежне розслаблення попередньо скорочених фенiлефрином каротидних артерiй гусака з динамiкою розвитку реакцiї аналогiчної EDHF. Отриманi результати вказують на те, що H2O2 функцiонує як EDHF у каротидних артерiях гусака, реалiзуючи свою дiю через Ca^2+-чутливi K^+-канали. It is shown that the nonselective inhibitors of heme-containing proteins (NaCN and Na2S) block the NO•-dependent relaxation, though they have no effect on the revealed EDHF component of acetylcholine vasodilatation, which excludes the functioning of heme-containing enzymes (soluble guanylate cyclase, NO•-synthase and other cytochrome P-450 monooxygenases) as EDHF-synthases. Catalase and 2-mercaptoethanol suppressed the EDHF-mediated relaxation. Exogenous H2O2 (10–100 μM) evoked the endothelium-independent relaxation of the goose carotid arteries preconstricted with phenylephrine with similar EDHF reaction dynamics. Therefore, H2O2 is functioning most likely as EDHF in goose carotid artery in response to ACh stimulation and makes a direct action on the Ca^2+-dependent K^+ channels.